Spontaneous activity of specific C-nociceptor subtypes from diabetic patients and mice: Involvement of reactive dicarbonyl compounds and (sensitized) transient receptor potential channel A1 - Becker, Anna; Babes, Alexandru; Düll, Miriam; Khalil, Mohammad; Kender, Zoltan; Gröner, Jan; Namer, Barbara; Reeh, Peter; Sauer, Susanne (Journal of the Peripheral Nervous System, 2023)
Background: Diabetic metabolism causes changes of the chemical milieu including accumulation of reactive carbonyl species, for example, methylglyoxal (MGO). MGO activates chemosensitive TRPA1 on nociceptors, but the contribution to neuronal pathophysiology causing pain and hyperalgesia in diabetic neuropathy is not fully understood. Methods: We employed single-nerve-fiber recordings in type 2 diabetes patients with (spDN) and without cutaneous pain (DN) and in streptozotocin-diabetic and healthy mice. In mice, we measured Ca++ transients in cultured DRG neurons and stimulated CGRP release from hairy skin. Results: In diabetic patients, we recorded a large proportion of pathologically altered nerve C-fibers (79%). In spDN patients we found a higher percentage (72%) of spontaneously active C-nociceptors than in DN patients (15%). The proportion of spontaneous activity was highest among pathological fibers with mechanoinsensitive fiber properties which are particularly sensitive to MGO in contrast to mechanosensitive fibers. Mouse polymodal nociceptors, in contrast to purely mechanosensitive C-fibers, showed highest prevalence of TRPA1-related chemosensitivity. In diabetic mice about 37% of polymodal nociceptors developed spontaneous activity and exhibited significantly greater MGO responses, indicating sensitized TRPA1 receptors. Low-threshold mechanosensitive Aδ-fibers were vigorously activated by MGO but independently of TRPA1 activation. Interpretation: Our translational findings suggest that TRPA1-expressing C-nociceptors, which in human correspond to mechanoinsensitive and in mice to polymodal nociceptors, are especially vulnerable to develop spontaneous activity. Those two different nociceptor classes might share the functional role as dicarbonyl-sensitive chemosensors and represent the critical nociceptor population that support the development of pain and hyperalgesia in diabetic neuropathy.
CRIS-Team Scopus Importer:2023-05-19
Keywords: calcitonin gene-related peptide; cutaneous nociceptor; excitability; mechanoinsensitive C-fiber; methylglyoxal; microneurography; neuropathic pain